Хижина дяди Тома - Бичер-Стоу Гарриет (Библиотека зарубежной классики, 1985)
Экземпляры: ЦБ/10 (20250121) / Инвентарный номер: 13199 / Цена: 2.30 / Сис.шифр: И(англ) / Авт.знак: Б 67 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)